Wear Properties Analysis on Al-Based Automotive Alloy with Varied Levels of Si in Dry, 3.5% NaCl and Seawater Corrosive Environments - A.A. Khan; M.S. Kaiser (Archives of Metallurgy and Materials)
The wear tests of aluminum based automotive alloys with different Si content in 3.5% NaCl, seawater and dry sliding environment are carried out. A conventional pin-on-disc wear apparatus is used at 2.55 MPa pressure and 0.51 m/s speed for a sliding distance of 923.2 m. The results show that the wear rate and friction coefficient of the alloy decreases with the increase of silicon content up to the eutectic point in all sliding environments. Among the different Si-rich intermetallics formed, especially Mg2Si strengthens the alloys. It is more prominent in the case of a corrosive environment through creating MgO plus SiO2 layers, which protect the corrosive wear and reduce the friction coefficient. Wear test surfaces have shown that Si addition makes the alloys wear-resistant with smooth abrasive grooves covered with oxides.